ANALYSIS FOLKLORE OF MANIK ANGKERAN: FUNCTIONAL AND RECEPTIVE APPROACH - I.I Km Ryanta Pramana Surya; Ni Made Diana Erfiani; Komang Tri Agustia (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2023)
The purpose of this study is to analyze the general structure of Balinese folktales. The research methodology used descriptive and qualitative, guided by Vladimir Propp’s theory of 31 Narrative Functions and a community reception approach proposed by Umar Junus 1985. Primary data for this research originates from Balinese folktales that were directly collected from the community, secondary sources were obtained from platform YouTube. The analysis reveals the Manik Angkeran story encompasses 10 out of the 31 narrative functions. The community's reception categorizes these stories as active, since still believed in and preserved within the community.